Realizing Justice through the Credit Restructuring Policy Due to The Spread of Covid-19 - Josua Navirio Pardede; Wigati Taberi Asih (Unram Law Review, 2020)
This study aims to find an overview of the bank credit restructuring policy and the realization of the fair value of the government policy. The stimulus provided was in the form of restructuring bank credit due to the spread of Covid-19. The research method used is a normative juridical research method with a statutory approach and a conceptual approach. This study uses secondary legal data in the form of primary legal materials, namely POJK No. 11 / POJK.03 / 2020, and secondary legal materials, namely books, journals, and other literature related to research problems. Based on the results of the study, it is known that the credit restructuring policy is an attempt by the government to provide legal protection for bank debtors who cannot fulfill their obligations to banks due to the spread of Covid-19. The realization of the value of justice in this credit restructuring policy is felt by all parties, the bank, and especially the debtor. The existence of a bank credit restructuring policy guarantees legal certainty to provide a sense of justice for debtors affected by Covid-19.